Amphiphilic Bioactives of Freshwater Aquatic Plants Nelumbo nucifera (Indian Lotus) and Lemna sp. with Antioxidant, Anti-Inflammatory and Antithrombotic Activities: In Vitro Study - Marina Seferli; Melina Lefkaki; Vasileios Manousakis; Anna Ofrydopoulou; Katie Shiels; Sushanta Kumar Saha; Grigorios Krey; Nikolaos Kamidis; Nikolaos Stamatis; Chryssa Anastasiadou; Alexandros Tsoupras (Pharmaceuticals)
Background-Objectives: Chronic diseases linked to inflammation, such as cardiovascular disease (CVD) and cancer, continue to pose major public health challenges due to their high mortality rates. There is growing interest in natural bioactive compounds, particularly those derived from plants, as potential therapeutic or preventive agents due to their low toxicity profiles. This study aimed to explore two freshwater plants—Nelumbo nucifera (Indian lotus) and Lemna sp.—as potential sources of bioactive compounds with antioxidant, anti-inflammatory, and antithrombotic properties. While N. nucifera has established but incompletely characterized biofunctional properties, Lemna sp. remains largely unexplored in this context. Methods: Amphiphilic extracts from both plant species were analyzed for phenolic and lipid constituents, including unsaturated fatty acids, polar lipids, and carotenoids. Antioxidant capacity was evaluated using DPPH, ABTS, and FRAP assays. Anti-inflammatory and antithrombotic activities were assessed via platelet aggregation assays using PAF and ADP agonists. Structural characterization was performed using Fourier transform infrared spectroscopy (FT-IR) and liquid chromatography–mass spectroscopy (LC-MS) to support structure–activity relationship (SAR) analysis. Results: Extracts, particularly from Lemna sp., showed potent antiplatelet activity against PAF and ADP. LC-MS revealed the presence of polar lipids rich in monounsaturated and omega-3 polyunsaturated fatty acids, with a favorable omega-6/omega-3 ratio, especially in Lemna sp., correlating with strong anti-inflammatory potential. High levels of total phenolics and carotenoids were observed, aligning with substantial antioxidant capacity in both species. Conclusions: These findings suggest that N. nucifera and Lemna sp. are promising sources of bioactive compounds with potential applications in functional foods, cosmetics, and pharmaceuticals targeting inflammation- and thrombosis-related chronic diseases. Further studies are warranted to confirm their safety and efficacy.